Analysis of forms of implementation of the concept of social responsibility of business in the conditions of combat actions in Ukraine - Evtushenko, A.; Tymohova, H.; Kurilenko, O. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2022)
By improving relations with the public, stakeholders, investors and authorities, corporate social responsibility has a significant impact on the ability of domestic and foreign companies to successfully develop and achieve economic competitiveness, as well as increase market share and create a positive image of the organization. By implementing various forms of social responsibility, the company realizes its contribution to the world of the future, solving local and global problems of humanity. Transparent two-way communication between enterprises becomes an effective tool that can significantly increase trust. The paper analyzes the forms of implementation of the concept of social responsibility of business in the conditions of hostilities in Ukraine. The results were obtained using the synthesis method, the official websites of the companies were analyzed, i.e. CSR sections, official pages of social networks (Facebook, Instagram), media publications, non-financial reports, CSR strategies, recommendations, policies and other publicly available documents. The study considered the influence of factors on decision-making by the company during the military operations in Ukraine according to the following criteria: adaptation of Ukrainian business, development of business strategies, official statement on the termination of cooperation with the Russian Federation. The impact of the total war of the Russian Federation against Ukraine on compliance/non-compliance with the policy of corporate social responsibility The considered features and results of using "Social Hub" and "impact investing" as a form of interaction between the enterprise and society. The implementation of the same form of KVS as "Social Hub" and "impact investing" provides not only financial support of the company for charitable purposes, but also contributes to the formation of a stable positive attitude among internal employees, thereby increasing the reputational capital of the business.